2018
DOI: 10.3855/jidc.10310
|View full text |Cite
|
Sign up to set email alerts
|

High seroprevalence of hepatitis E among pigs suggests an animal reservoir in Cameroon

Abstract: Introduction: Hepatitis E virus (HEV) is one of the most prevalent cause of acute hepatitis in humans worldwide. The risk of HEV transmission is not limited only to spread from human to human but the infection can also spread from animals to humans, especially from the domestic pigs. Despite mounting evidence regarding the zoonotic potential of porcine HEV infection, there are limited data on its prevalence in pigs in the sub-Sahara Africa region. Therefore, the present study aimed to determine the seroprevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
3
6
0
Order By: Relevance
“…This difference may also be associated with the different HEV diagnostic methods used in these different studies. Our study shows high seroprevalence of IgM (21.0%) compared to IgG (17.7%) similarly to the previous study by Modiyinji et al [12]. This could be explained by the fact that majority of the pigs in this study were older than 6 months, since, Seminati et al in 2008 shows that pigs older than 12 weeks of age have a higher IgM seroprevalence, compared to IgG seroprevalence [17].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This difference may also be associated with the different HEV diagnostic methods used in these different studies. Our study shows high seroprevalence of IgM (21.0%) compared to IgG (17.7%) similarly to the previous study by Modiyinji et al [12]. This could be explained by the fact that majority of the pigs in this study were older than 6 months, since, Seminati et al in 2008 shows that pigs older than 12 weeks of age have a higher IgM seroprevalence, compared to IgG seroprevalence [17].…”
Section: Discussionsupporting
confidence: 88%
“…There is accumulated evidence that HEV is enzootic in a broad range of animals in Cameroon. Serological analyses have revealed the presence of anti-HEV antibodies among pigs and nonhuman primates in previous studies in Cameroon [12,13]. We noted high anti-HEV seropositivity in this study of 47.7% similarly to the 43.2% that was previously reported in the North and West regions of Cameroon [12], confirming that pigs are indeed a main reservoir for HEV.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…All samples were tested for the presence of anti‐HEV antibodies with an enzyme‐linked immunosorbent assays (ELISA): HEV immunoglobulin G (IgG) ELISA and HEV immunoglobulin M (IgM) ELISA 3.0 kits (MP Biomedicals Asia Pacific Pte Ltd, Singapore; formerly Genelabs Diagnostics Pte). The test was carried out according to the manufacturer's instructions and assay validity was evaluated according to the manufacturer's specifications as previously described …”
Section: Methodsmentioning
confidence: 99%
“…Hepatitis E virus (HEV) is also widespread among pigs. A serological study found that 70 out of 162 pigs sampled were positive for HEV [156]. The study suggested the pigs were the animal reservoir of HEV in Cameroon [156].…”
Section: Cameroonmentioning
confidence: 98%